Wave Labyrinth Weir: A New Shape Spillway to Minimize the Effect of the Vertex Angle - Tanga, Arody; Ishak, Muhammad Galib; Arafat, Yassir (International Journal of Integrated Engineering, 2025)
Increasing the discharge capacity of spillway structures is essential for efficient water management and flood control. This can be achieved in various ways, one of which is by lengthening the spillway crest. Labyrinth weirs, which provide a longer crest length compared to linear weirs within the same channel width, are commonly designed in trapezoidal, triangular, or rectangular forms. However, the convergence of the weir walls at sharp vertex angles tends to reduce discharge capacity. To address this limitation, a new wave labyrinth weir design—free of sharp corners—was proposed in this study to minimize the adverse effects of vertex angles. The shape of the wave labyrinth weir was derived from the cosine wave equation. The influence of the vertex angle was evaluated based on the discharge coefficient (Cd) at various upstream heads. The experimental investigation was conducted under free-flow conditions in a rectangular flume measuring 4.80 meters in length, 50 centimeters in width, and 40 centimeters in depth. Two physical models were fabricated using acrylic: a basic triangular labyrinth weir and the proposed wave labyrinth weir. Both models shared the same crest length (L = 87 cm) and height (P = 10 cm). Flow measurements were obtained through point gauge readings and the Thomson weir method. The results showed that the maximum discharge coefficient (Cd max) for the wave labyrinth weir reached 0.88, compared to 0.82 for the triangular labyrinth weir. This confirms that the wave labyrinth weir effectively reduces the negative impact of vertex angles on discharge performance. In addition, the wave configuration contributed to smoother nappe flow and reduced turbulence, suggesting greater flow stability compared to the conventional design.